2022
DOI: 10.1002/ehf2.14128
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of cardiogenic shock secondary to culprit left main coronary artery lesion‐related myocardial infarction

Abstract: Aims This study aimed to assess, in patients with cardiogenic shock secondary to unprotected left main coronary artery‐related myocardial infarction (ULMCA‐related AMICS), the incidence and predictors of no recovery of left ventricular function during the admission. Methods and results This was an observational study conducted at two tertiary care centres (2012–20). The main outcome measured was death or requirement for heart transplantation (HT) or left ventricular ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 31 publications
0
4
2
Order By: Relevance
“…In the abovementioned studies and the present study, the only common predictor significantly associated with reduced 30-day survival was successful reperfusion (final TIMI flow 3). Although in the present study, the use of mechanical support was found to be associated with 30-day mortality, in the studies by Galván-Román et al [ 40 ] and Gutiérrez-Barrios et al [ 20 ], this was not observed. In the study by Galván-Román et al [ 40 ] and the present study, mechanical support was inserted before PCI in the majority of cases.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…In the abovementioned studies and the present study, the only common predictor significantly associated with reduced 30-day survival was successful reperfusion (final TIMI flow 3). Although in the present study, the use of mechanical support was found to be associated with 30-day mortality, in the studies by Galván-Román et al [ 40 ] and Gutiérrez-Barrios et al [ 20 ], this was not observed. In the study by Galván-Román et al [ 40 ] and the present study, mechanical support was inserted before PCI in the majority of cases.…”
Section: Discussioncontrasting
confidence: 76%
“…Although in the present study, the use of mechanical support was found to be associated with 30-day mortality, in the studies by Galván-Román et al [ 40 ] and Gutiérrez-Barrios et al [ 20 ], this was not observed. In the study by Galván-Román et al [ 40 ] and the present study, mechanical support was inserted before PCI in the majority of cases. In line, a systematic review and meta-analysis showed that routine use of IABP in STEMI patients complicated by cardiogenic shock is conflicting [ 42 ].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations